The Influence of Students’ Reading Interest on Writing Ability in Learning Indonesian - Sela Dwi Anjani; Sukarno Sukarno; Vebbi Andra (Jadila: Journal of Development and Innovation in Language and Literature Education, 2022)
The problems discussed in this study aim to determine whether there is an effect of reading interest in science majors on writing skills in learning Indonesian at SMA Negeri 5 Lebong. The approach in this research is quantitative and the type of research used is regressional. The population of this study were students majoring in science at SMA Negeri 5 Lebong and the sample of this study amounted to 65 students. The variables in this study consisted of the independent variable, namely reading interest and the dependent variable, namely the ability to write. The data collection technique was carried out by distributing a questionnaire (questionnaire) for the variable X and a poetry writing test for the Y variable. For testing the validity and reliability of this study using the SPSS version 20 program. Based on the results of data analysis, the t- count value obtained is 5.519 and the t- table is 1.998 , then the t- count value is 5.519 > from t- table 1.998, so it can be concluded that H o rejected and H a acceptability which means "There is the influence of interest in reading (X) on the ability to write (Y) in the Indonesian language learning in SMAN 5 Lebong".